The effect of silver nitrate on the alkaline phosphatase activity, TNF and IL-10 gene expression; Experimental and computational studies - Nader jadid; Ali Asghar Moshtaghie; Hashem Nayeri; Masoud Foladgar; Maryam Ostadsharif (Heliyon)
The present study examines the effects of silver nitrate on the activity of the enzyme alkaline phosphatase (ALP) and its regulatory influence on inflammatory cytokines, specifically interleukin-10 (IL-10) and tumor necrosis factor-alpha (TNF-α). These parameters are critical for elucidating the biochemical and immunological responses associated with metal exposure. The research employed enzyme-linked immunosorbent assay (ELISA) techniques to quantify IL-10 and TNF-α levels using serum assay kits. Additionally, gel filtration chromatography with Sephacryl S300 demonstrated that serum from silver nitrate-treated groups exhibited a significantly elevated concentration of high molecular weight alkaline phosphatase compared to control groups. In the TNF-α ELISA assay, no significant differences were observed between the control and treatment groups 15 days post-injection of silver nitrate. However, a statistically significant alteration was detected in both groups 45 days post-injection (P < 0.005). Molecular docking analysis further revealed that the optimal binding pose for ALP, based on the docking score, was −5.28 kcal/mol, with a re-ranking score of −7.43 kcal/mol. Collectively, the findings indicate that silver nitrate exerts a significant impact on ALP activity, leading to a sustained increase in TNF-α levels over time, while IL-10 levels remain unaffected.